Sentiment Analysis of Public Opinion in Indonesia on China's Belt Road Initiative - Anang Masduki; Panqiang Niu; Muhammad Hamka; Zalik Nuryana (ULTIMA Comm, 2026)
This research wants to answer the growing public opinion in Indonesia about the Belt Road Initiative project. The data source used is social media twitter with content analysis as a research method. Twitter data from January 2016 to September 2021 is limited to the Indonesian language and Indonesian territory. From the results of data mining using Python with search keywords: "Chinese foreign workers," "China OBOR project," "China investment," "China infrastructure," and "China debt," there are 37,149 tweets. Sentiment analysis shows the number of positive tweets is 8.119 or 21.86%, Neutral 4.766 or 12.83%, and negative 24,264 tweets or 65.32%. The research analysis results show that public communication and support groups are inferior. It can be seen from the narration and the issues that are built that are not focused so that it appears that there is no coordination. Second, strengthening opposition groups that unite and support each other raises an issue to master the narrative on social media. Third, Indonesia adheres to a democratic system, so it is necessary to abandon the ways of threatening, intimidating, and repressing people who criticize the BRI project.